Inflammation, malignancy and immunology in gastrointestinal spindle cell tumors: What is beyond GIST? Entzündung, Malignität und Immunologie gastrointestinaler Spindelzelltumoren: Was gibt es abgesehen von GIST noch? - Montgomery, E.; Voltaggio, L.; Vieth, Michael (Pathologe, 2014)
Many mesenchymal tumors and tumefactions associated with the gastrointestinal tract feature prominent inflammatory cells but the mechanisms for the inflammation and the processes themselves remain poorly understood. Such classic lesions include Kaposi sarcoma, inflammatory fibroid polyp, sclerosing mesenteritis and inflammatory myofibroblastic tumor but, more recently, the recognition of IgG4-related fibrosclerosing disease has resulted in modification of the views on pathogenesis and treatment of such inflammatory lesions in many anatomical sites. In some lesions the inflammation may reflect viral influences (Kaposi sarcoma) or a bacterial infectious trigger (IgG4-related fibrosclerosing disease) whereas in others such an interaction is unclear and alterations in various genes have been detected, such as anaplastic lymphoma receptor tyrosine kinase gene rearrangements in inflammatory myofibroblastic tumor and platelet-derived growth factor receptor alpha (PDGFRA) gene mutations in inflammatory fibroid polyp and some gastrointestinal stromal tumors (GIST). Even the inflammatory milieu of GISTs may have an impact on the outcome. This article discusses the practical diagnostic considerations as well as the theoretical background.
CRIS-Team Scopus Importer:2025-03-05
Keywords: GI tract; Histology; Mesenchymal tumors; Polyps; Prognosis